Capability of the Liquid Penetrant Method to Detect Defects in Welds (LACCEI, 2024)
The dye penetrant test is widely used because of its ease in revealing the presence of surface defects in welded components to ensure that their quality complies with industry standards. Since the various penetrant materials and the characteristics of the elements to be inspected produce uncertainty in the detection, it was proposed to determine the ability of the dye penetrant method to reveal defects in welded joints by varying the testing technique. Tests were performed on structural steel welded joints containing surface defects, characterized by microscopy, applying the visible and fluorescent penetrant techniques. The estimation of the detection capability of each technique was performed by the statistical model POD assisted with Software mh1823POD, obtaining detection probability curves and a50, a90 and a90/95 values to compare the effectiveness of each testing technique. The results showed that the fluorescent penetrant inks, with respect to the visible ones, present an improvement in their capacity to detect the smallest defects, in a reliable way, forming precise relevant indications to the real size of the defect.